The late pleistocene cave bear fauna of the Torrener Bärenhöhle in the northern alps (Salzburg, Austria). (2nd November 2021) - Döppes, Doris; Alberti, Federica; Barlow, Axel; Krutter, Sebastian; Friedrich, Ronny; Hofreiter, Michael; Lindauer, Susanne; Kavcik-Graumann, Nadja; Rosendahl, Wilfried; Rabeder, Gernot
ABSTRACT: The Torrener Bärenhöhle (Cave of Torren) is an alpine bear cave in the limestone Alps near Salzburg (Austria). The entrance of this cave is located in the riverbed of a periodically flowing stream that floods the caverns during snowmelt or after heavy rainfall. Due to these flooding events, the fossiliferous layers were repeatedly destroyed and the fossil remains – mainly cave bear bones – were distributed over the cave's entrance hall. The fossil collections have taken place since 1924. During the last decades, numerous bones scattered over the cave floor have been collected again and again. In this study, we conduct metric and morphological analyses of this fossil material as well as DNA analyses in an attempt to clarify the taxonomic position of the cave bear remains. The chronological status of the bear remains has not yet been clarified, because the few samples that have been analysed so far were beyond the range of 14 C dating, indicating they are older than 49, 000 cal yr BP. The following taxa are represented in small numbers: Brown bear (Ursus arctos L.), wolf ( Canis lupus L.), cave lion ( Panthera spelaeus Goldfuss, 1810), European bison ( Bison bonasus L.) and beaver ( Castor fiber L.).